Human Immune Responses and the Natural History of Neisseria gonorrhoeae Infection - Lovett, Angela; Duncan, Joseph A. (Frontiers in Immunology, 2019)
The intimate relationship between humans and Neisseria gonorrhoeae infections span centuries, which is evidenced in case reports from studies dating back to the late 1700s and historical references that predate medical literature. N. gonorrhoeae is an exclusive human pathogen that infects the genital tract of both men and women as well as other mucosal surfaces including the oropharynx and rectum. In symptomatic infections, N. gonorrhoeae induces a robust inflammatory response at the site of infection. However, infections can also present asymptomatically complicating efforts to reduce transmission. N. gonorrhoeae infections have been effectively treated with antibiotics since their use was introduced in humans. Despite the existence of effective antibiotic treatments, N. gonorrhoeae remains one of the most common sexually transmitted pathogens and antibiotic resistant strains have arisen that limit treatment options. Development of a vaccine to prevent infection is considered a critical element of controlling this pathogen. The efforts to generate an effective gonococcal vaccine is limited by our poor understanding of the natural immunologic responses to infection. It is largely accepted that natural protective immunity to N. gonorrhoeae infections in humans does not occur or is very rare. Previous studies of the natural history of infection as well as some of the humoral and cellular immune responses to infection offer a window into the issues surrounding N. gonorrhoeae vaccine development. In this review, we summarize the current body of knowledge pertaining to human immune responses to gonococcal infections and the role of these responses in mediating protection from N. gonorrhoeae.